2010
DOI: 10.1590/s1984-46702010000600010
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology in the starfish Echinaster (Othilia) guyanensis (Echinodermata: Asteroidea) in southeastern Brazil

Abstract: Echinaster (Othilia) guyanensis Clark, 1987 is an endangered starfish distributed throughout the Caribbean and Atlantic Ocean. Even though it has been extensively harvested, little is known about the biology and ecology of this starfish. Here, we examine reproduction seasonality in E. (O.) guyanensis. Individuals were collected monthly for one year, including four complete lunar phases. The gonad index (GI) was calculated to determine annual and monthly reproductive peaks. Gametogenesis stages were also determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Most gametogenic stages did not differ between sexes in the GI values. It has been reported that some asteroid species have higher GI values in females than in males (Carvalho & Ventura, 2002;Pastor de Ward et al, 2007;Bos, Gumanao, Alipoyo & Cardona, 2008;Benítez-Villalobos & Martínez-García, 2012) while others show higher values in males than in females (Benítez-Villalobos & Díaz-Martínez, 2010) or even no difference between the sexes (Georgiades, Temara & Holdway, 2006;Benítez-Villalobos, Díaz-Martínez & Tyler, 2007;Mariante, Lemos, Eutrópio, Castro & Gomes, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Most gametogenic stages did not differ between sexes in the GI values. It has been reported that some asteroid species have higher GI values in females than in males (Carvalho & Ventura, 2002;Pastor de Ward et al, 2007;Bos, Gumanao, Alipoyo & Cardona, 2008;Benítez-Villalobos & Martínez-García, 2012) while others show higher values in males than in females (Benítez-Villalobos & Díaz-Martínez, 2010) or even no difference between the sexes (Georgiades, Temara & Holdway, 2006;Benítez-Villalobos, Díaz-Martínez & Tyler, 2007;Mariante, Lemos, Eutrópio, Castro & Gomes, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…In Santa Catarina, the starfish Echinaster (Othilia) brasiliensis was identified in 29 sites, recorded by 14 scientific references (Table 1). In Brazil, three Othilia species have been recorded, Othilia brasiliensis (Tommasi, 1970b;Hopkins et al, 2003;Netto et al, 2005;Lima & Fernandes, 2009;Gondim et al, 2011Gondim et al, , 2020Miranda et al, 2012;Ventura et al, 2013;Alitto et al, 2016), Othilia guyanensis (Hopkins et al, 2003;Mariante et al, 2010;Ventura et al, 2013) and Othilia echinophorus (Tommasi, 1970b;Alves & Cerqueira, 2000;Hopkins et al, 2003;Gondim et al, 2008Gondim et al, , 2011Gondim et al, , 2020Lima & Fernandes, 2009;Miranda et al, 2012;Ventura et al, 2013). However, according to the phylogenetic study by Lopes et al (2016), O. brasiliensis and O. guyanensis should be synonymized, and the status of O. echinophorus should be reviewed; the authors emphasize the large morphological variability and phenotypic plasticity of the genus Echinaster, and support the raise of the genus Othilia, previously demoted to subgenus (Clark & Tortonese, 1986).…”
Section: Taxonomic Informationmentioning
confidence: 99%
“…Asterinid species have different reproductive patterns, including seasonal or continuous breeding periodicity (Carvalho and Ventura, 2002;Barker and Xu, 1991b;Byrne, 1992;Paik et al, 2005;Pastor-de-Ward et al, 2007;Mariante et al, 2010;Micael et al, 2011;Benítez-villalobos and Martínez-garcía, 2012). The differences are related to many environmental factors, including temperature, hydrodynamics, the quantity and quality of available food, and photoperiod.…”
Section: Introductionmentioning
confidence: 99%